The Influence of Informational and Emotional Advertising Appeals on Advertising Effectiveness – Consumers’ Perspective on the Over-the-Counter Product Advertisements in Finland - Nokelainen, Elina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Consumers face enormous amounts of promotional messages daily whereas the pharmaceutical companies among other industries spend considerable time and money developing effective advertising strategies. There are multiple possible ways to appeal the target customer in order to increase the effectiveness of the advertisement. In spite of the various possibilities to categorize persuasive communication, the informational and the emotional appeals are the typical approaches. This study assesses the influence of the informational and emotional advertising appeals on the advertising effectiveness in the context of OTCs in Finland. The research method applied in this study is a quantitative survey. The data consists of 461 responses from the target population of 18–80 years old Finnish speaking consumers. The results from the marketing research indicate that the positive correlations of the emotional appeals are much stronger than the positive correlations of the informational appeals relating to the advertising effectiveness. However, on average the Finnish consumers experience the OTC advertisements relying on the informational appeals more effective than the OTC advertisements relying on the emotional appeals. Furthermore, within emotional appeals there is a much greater variety in the experienced advertising effectiveness not providing as stabile and consistent experienced advertising effectiveness compared to the informational appeals. Thus, the OTC advertisement relying more on the emotional appeals are much more risky in terms of advertising effectiveness. There are also differences with the experienced advertising effectiveness between the Finnish consumer groups and the information can be utilised when designing tailored OTC advertisements. The Finnish men consider humorous advertisements more effective than the Finnish women. In addition, the people living outside Uusimaa Region experience higher advertising effectiveness with the advertisements relying more on the informational advertisements compared to the people living in Uusimaa Region. In similar vein, the people with lower education experience higher advertising effectiveness with the advertisements relying more on the informational advertisements compared to the people with high education. Additionally, the older generation perceive an OTC advertisement with a middle-aged celebrity more effective than the younger consumers

Kuluttajat kohtaavat huomattavia määriä mainontaa päivittäin. Lääkealan yhtiöt kuluttavat muiden yhtiöiden tavoin merkittävästi aikaa ja rahaa kehittääkseen tehokkaita mainonnan strategioita. Mainonnan kohderyhmän huomio voidaan kiinnittää monilla erilaisilla tehokeinoilla, jotka kasvattavat mainonnan tehokkuutta. Informationaaliset ja emotionaaliset mainonnan tehokeinot ovat tyypillisimmät lähestymistavat. Tämä markkinointitutkimus tarkastelee informationaalisten ja emotionaalisten mainonnan tehokeinojen vaikutusta itsehoitovalmisteiden mainonnan tehokkuuteen suomalaisen kuluttajan näkökulmasta. Tutkimus on toteutettu kvantitatiivista menetelmää hyödyntäen. Aineiston perustana toimivat 461:n satunnaisotannalla valitun kuluttajan vastaukset. He ovat 18–80-vuotiaita ja suomenkielisiä. Tulokset osoittavat emotionaalisten tehokeinojen voimakkaampaa positiivista korrelaatiota mainonnan tehokkuuteen verrattuna informationaalisiin tehokeinoihin. Suomalaiset kuluttajat kokevat keskimäärin informationaalisiin tehokeinoihin nojautuvat mainokset tehokkaampina, kuin emotionaalisiin tehokeinoihin nojautuvat. Mielipiteet emotionaalisia tehokeinoja hyödyntävien mainosten tehokkuudesta kuitenkin vaihtelevat huomattavasti enemmän verrattuna informationaalisia tehokeinoja hyödyntäviin mainoksiin. Siksi emotionaalisia tehokeinoja sisältävät mainokset eivät takaa tasaista ja johdonmukaista mainonnan tehokkuutta, mikä tekee niistä paljon riskialttiimpia mainostajan kannalta katsottuna. Suomessa kuluttajaryhmät eroavat selvästi toisistaan koetussa mainonnan tehokkuudessa, mikä auttaa mainonnan räätälöinnissä oikeaa kohderyhmää varten. Suomalaiset miehet kokevat huumoripitoiset mainokset tehokkaammiksi kuin naiset. Lisäksi Uudenmaan maakunnan ulkopuolella asuvat suomalaiset kokevat mainokset, jotka nojaavat enemmän informationaalisiin tehokeinoihin tehokkaampina kuin Uudellamaalla asuvat kuluttajat. Samoin suomalaiset, joilla on matala koulutusaste, kokevat informationaalisiin tehokeinoihin nojaavat mainokset tehokkaampana kuin ihmiset, joilla on korkea koulutusaste. Lisäksi vanhempi väestö kokee keski-ikäisen julkisuuden henkilön edustaman itsehoitovalmistemainoksen tehokkaammaksi kuin nuorempi suomalainen väestö